Determinant Analysis of Health Promotion on Stress Incidence among Older Adults in Manggenae Village, Dompu - Affan, Muhammad; Iranas, Ady; Mutmainni; Irawan, Bambang (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
The escalating global elderly population presents significant health challenges, with stress incidence being a critical concern. This study aimed to analyze the determinants of health promotion influencing stress levels among older adults in Manggenae Village, Dompu Regency, Indonesia. Employing a quantitative, cross-sectional design, data were collected from 82 elderly individuals (≥60 years) via total sampling using validated questionnaires measuring stress, health education, social support, and healthcare professional roles. Analyses included univariate, bivariate (Chi-square), and multivariate (binary logistic regression). The findings revealed that 52.4% of participants experienced severe stress. Bivariate analyses demonstrated significant associations (p<0.001) between health education, social support, and healthcare professional involvement with stress levels. Specifically, adequate health education and perceived professional support were linked to lower stress, while a lack of social support correlated with higher stress. Multivariate analysis identified the role of healthcare professionals as the most dominant factor influencing elderly stress (Wald=16.456, p<0.001), with an Exp(B) of 0.026, indicating a substantial reduction in the risk of severe stress. These results underscore the critical need for proactive health promotion, emphasizing enhanced engagement of healthcare professionals in rural Indonesian communities to mitigate stress and improve geriatric mental well-being through robust community-based interventions for sustainable elderly mental health outcomes.